Sequential fetal serum β2‐microglobulin to predict postnatal renal function in bilateral or low urinary tract obstruction. (29th March 2017) - Spaggiari, E.; Faure, G.; Dreux, S.; Czerkiewicz, I.; Stirnemann, J. J.; Guimiot, F.; Heidet, L.; Favre, R.; Salomon, L. J.; Oury, J. F.; Ville, Y.; Muller, F.
ABSTRACT: Objective: Fetal serum β 2‐microglobulin has been shown to predict postnatal renal outcome in cases of fetal obstructive uropathy. We assessed the value of serial measurements of fetal serum β 2‐microglobulin in the prediction of postnatal renal outcome. Methods: We retrospectively studied renal outcome in 42 fetuses with bilateral or low urinary tract obstruction that had fetal blood sampling on at least two occasions to assay serum levels of β 2‐microglobulin. Amniotic fluid volume at the time of each sampling was recorded. We classified renal outcome as either favorable (when postnatal renal function was normal) or adverse (when postnatal chronic renal failure occurred or when renal dysplasia at autopsy was noted). A β 2‐microglobulin cut‐off of 5 mg/L and amniotic fluid index of 5 cm were used to predict postnatal renal outcome. Results: Renal outcome was adverse in 28 cases and favorable in 14. In 12 (28.6%) cases, fetal serum β 2‐microglobulin concentration differed between the first and last measurement. Prediction of postnatal renal outcome was correct in 11 of these cases based on the last β 2‐microglobulin measurement. The sensitivity of β 2‐microglobulin in predicting renal outcome was significantly higher ( P = 0.005) when using the last rather than the first measurement (96.4% vs 64.3%), with similar specificity for both measurements (85.7% vs 78.6%, non‐significant). The sensitivity of amniotic fluid volume was also significantly higher ( P = 0.005) when using the last rather than the first measurement (75.0% vs 35.7%), with similar specificity for both measurements (64.3% vs 71.4%, non‐significant). Conclusion: Sequential measurement of serum β 2‐microglobulin, performed for adverse ultrasound findings, such as renal parenchymal abnormality or decreasing amniotic fluid volume, predicts postnatal renal outcome more accurately than does a single assay. This may be due to possible worsening of renal injury with increasing duration of urinary tract obstruction. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.